Pengetahuan Tentang Anemia pada Remaja dan Dewasa Muda di Jakarta dan Jawa Barat: Survei Demografi dan Kesehatan Indonesia 2017 - Mugia Bayu Rahardja; Edhyana Sahiratmadja; Elsa Pudji Setiawati; Ramdan Panigoro; Indra Murty Surbakti (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2024)
Introduction: Iron deficiency anemia in developing countries is common. However, knowledge on the etiology of anemia among young adults needs to be further explored, including hemoglobinopathy, since Indonesia is located in the thalassemia belt, harboring 6-10% thalassemia carriers. The study aimed to explore the knowledge about anemia among young adults in Jakarta and the province of West Java. Methods: A descriptive analytical study design using secondary data from the National Demographic and Health Survey 2017 was employed. A questionnaire was distributed to unmarried young adults (n=5389) aged 15-24, including questions about anemia. Knowledge was further compared between places, genders, and age groups. Result: Only 70% of young adults have heard about anemia. However, the knowledge was poor. The definition of anemia was lack of blood (48%), and only 5% stated it was due to iron deficiency. The etiology of anemia was lack of vegetables (21%) and meat (18%) consumption. As a treatment, only 9% mentioned the iron tablets. None mentioned thalassemia carrier as an alternative cause of anemia. Conclusion: Young adults in Jakarta and West Java are poorly informed about anemia. Socialization to increase knowledge about anemia is imperative. Thalassemia carriers need to be introduced among unmarried young adults for better family planning in the future.